THE APPLICABILITY OF 20TH CENTURY ANALYTICAL METHODS FOR MUSIC OF ANY STYLE, INCLUDING JAZZ (Mūzikas akadēmijas raksti, 2024)
Learning to perform any new musical work is a multi-dimensional task for any musician, young or old, experienced or novice. In most academic situations (as opposed to improvisatorial situations typical for jazz and popular music), the musician must acquire all of the needed musical information from the notated score, and translate that to actual performance. This process can be expedited and made more accurate if analytical methods are employed in studying the musical score. In addition, analysis can give important clues as to how the musician can better interpret the music he or she is performing. Analytical methods developed by Heinrich Schenker, Felix Salzer, and Paul Hindemith offer approaches to better hear and interpret musical works of many widely differing styles and genres. These methods support the ideas of guide-tone lines proposed by jazz theorists. The examination of analytical methods shows how musical information can be more easily grouped, filtered, ordered, and re-structured. This information can be a useful tool for any music teacher and performer. Music can be learned without much analysis, but then the process of learning will be slower and less insightful. Analysis can offer clues as to how one can better interpret music and perform with greater confidence, understanding, and emotional freedom.